Texting banned for commercial drivers - Lindenberger, Michael A; Benning, Tom (McClatchy - Tribune News Service, 2010)
Obama's transportation secretary on Tuesday banned truckers and commercial bus drivers from sending and receiving text messages, leaving the Texas Department of Public Safety scrambling to figure out how to enforce it. [...] Tuesday's announcement makes sending, or even reading, a text message while driving a federal safety offense, too, and could put some commercial drivers at risk of losing their authority to operate -- plus subject them to fines of up to $2,750 for each offense.